(untitled) (Canadian Eye Care Today, 2023)
Keratoconus (KC) is a condition which results in progressive corneal thinning. It was first discovered by Dr. John Nottingham in 1854 who described it as “conical cornea” due to the outward bowing appearance caused by the condition. The prevalence of KC is between 0.2 and 4,790 per 100,000 people. KC does not have a gender predilection. It is believed to appear more commonly in South Asian and Middle Eastern populations. Keratoconus typically begins in the second and third decades of life although it can develop at any time. The clinical symptoms of the condition include blurred and distorted vision. Patients may present with higher-order aberrations (HOA) ̶ the most characteristic of which is coma ̶ resulting in blurred and double vision. The common signs of KC include corneal protrusion and thinning, prominent corneal nerves, Fleischer ring, Vogt’s striae, and scissors reflex on retinoscopy. The most frequently encountered phenotype is oval cones in the central cornea. The primary diagnostic tool for KC is corneal topography, although pachymetry, including epithelial mapping and corneal tomography, are often performed in conjunction with each other as they aid with early detection and the monitoring of KC progression. Advancements in clinicians’ knowledge of KC and expertise in its treatment, have led to novel therapies. Stopping disease progression is now possible and improving patients’ quality of vision is feasible in many cases. Preventive measures halting progression and management of mild and moderate forms of KC are reviewed. Treatment of severe KC will also be briefly reviewed.